2020
DOI: 10.1177/0046958020917491
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals’ Perceptions of Pay-for-Performance in Practice: A Qualitative Metasynthesis

Abstract: Incentive-based pay-for-performance (P4P) models have been introduced during the last 2 decades as a mechanism to improve the delivery of evidence-based care that ensures clinical quality and improves health outcomes. There is mixed evidence that P4P has a positive effect on health outcomes and researchers cite lack of engagement from health care professionals as a limiting factor. This qualitative metasynthesis of existing qualitative research was conducted to integrate health care professionals’ perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
13
0
3
Order By: Relevance
“…Tunnel vision Emphasis is placed on dimensions of performance that are measured or incentivized, while other unmeasured but important aspects are overlooked [ 2 , 3 , 5 , 10 , 13 , 14 , 28 , 30 39 ] ✓✓ b. Measure fixation Emphasis is placed on meeting the performance target rather than the associated objective [ 2 , 3 , 5 , 10 , 26 , 28 , 32 , 33 , 38 , 40 42 ] ✓✓ c. Suboptimization Focusing on one component of a total and making changes intended to improve that one component and ignoring the effects on other components (e.g., pursuit of narrow local objectives at the expense of broader organizational or system objectives) [ 2 , 10 , 33 , 41 ] d. Myopia Excessive concentration on short-term targets without consideration for long-term consequences [ 2 , 5 , 10 , 33 , 41 , 43 ] e. Quantification privileging Fixation on data that can be quantified causing qualitative aspects of healthcare to be missed [ 5 , 34 , 44 ] f. Anachronism Lag effect between data capture and data usage causes data to not help solve current problems [ 5 ] g. Insensitivity Asse...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunnel vision Emphasis is placed on dimensions of performance that are measured or incentivized, while other unmeasured but important aspects are overlooked [ 2 , 3 , 5 , 10 , 13 , 14 , 28 , 30 39 ] ✓✓ b. Measure fixation Emphasis is placed on meeting the performance target rather than the associated objective [ 2 , 3 , 5 , 10 , 26 , 28 , 32 , 33 , 38 , 40 42 ] ✓✓ c. Suboptimization Focusing on one component of a total and making changes intended to improve that one component and ignoring the effects on other components (e.g., pursuit of narrow local objectives at the expense of broader organizational or system objectives) [ 2 , 10 , 33 , 41 ] d. Myopia Excessive concentration on short-term targets without consideration for long-term consequences [ 2 , 5 , 10 , 33 , 41 , 43 ] e. Quantification privileging Fixation on data that can be quantified causing qualitative aspects of healthcare to be missed [ 5 , 34 , 44 ] f. Anachronism Lag effect between data capture and data usage causes data to not help solve current problems [ 5 ] g. Insensitivity Asse...…”
Section: Resultsmentioning
confidence: 99%
“…Positive Unintended Consequences c. Improved morale Feeling of recognition and increased confidence and pride in individual or organizational performance [ 13 , 16 , 40 , 61 ] d. Motivated learning and development PM spurs further education and training to support improvement [ 13 , 27 ] e. New relationships and collaborative problem-solving Professionals, organizations, or networks come together in new and inventive ways to cope with PM [ 9 , 26 , 36 ] ✓✓ f. Improved capacity planning Information collected through PM allows for better internal planning and external applications N/A Unintended Consequences on Patients and Patient Care I. Inappropriate or Sub-Optimal Care a. Clinical decisions driven by PM (rather than by evidence and clinical judgment) PM generates pressure to diagnose and treat patients in particular ways, resulting in under-treatment, over-treatment, and/or harm to patient [ 9 , 12 , 13 , 15 , 27 , 28 , 38 , 40 , 49 , 50 , 56 , 57 , 62 64 ] b. Improved documentation without improved care Providers document care provided more effectively, but the care itself is not improved [ 6 , 13 , 39 , 49 , 54 , 55 ] c. Less continuity of care When PM incen...…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the evaluating indicators seem quite unreasonable, and they are often asked to complete lots of unnecessary forms because the bonus (A8), which gradually lead to 'gaming' by reporting services that were not provided or 'crowding out' by investing all their energy into the remunerated activities while neglecting others necessary (A3 and A6-A9). Therefore, appropriate indicators and consistent evaluation of the performance of and adjustments to incentivized measures are needed, which will allow institutions to shift focus and attention to areas in greatest need of improvement, so as to mitigate or even avoid the unintended consequences (Martin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nurse and physician perception and engagement in the pay-for-performance model design and implementation have been cited as an important factor that may affect programme outcomes (Martin et al, 2020). Insight into their perceptions will help to make clear the impacts on motivations, negative effects and the whole implement process.…”
mentioning
confidence: 99%
“…However, a 2011 Cochrane review found insufficient evidence to either support or discourage the use of provider financial incentives to improve quality metrics in primary care [ 40 ]. Cultural attitudes may also lead providers and healthcare staff to ambivalently or negatively perceive the influence of provider financial incentives [ 41 ]. This may explain why few PCPs and clinical staff endorsed provider financial incentives as having a high impact on teleophthalmology use despite our data supporting its effectiveness in this study.…”
Section: Discussionmentioning
confidence: 99%